15 POSSIBLE ROLE OF MATERNAL LYMPHOCYTES CONTAINED IN BREAST MILK IN THE DEVELOPMENT OF AUTOIMMUNE DISEASES. (1st March 2005) - Cohen, A. M.; Pancake, B. A.; Zucker-Franklin, D.
Abstract : Normal colostrum and breast milk contain viable leukocytes. Colostrum contains about 10, 000 lymphocytes per mm3 of which 20% consist of T lymphocytes. After lactation is fully established, milk contains about 100, 000 lymphocytes per mm3. Because gastric acidity and enzyme concentrations are very low in the newborn infant, lymphoid cells survive in its stomach and intestine and have been shown to cross the mucosal wall. If the maternal lymphocytes are allo-typically different from those of the infant, such cells could infiltrate tissues and play a role in the development of autoimmune diseases in later life. Studies in animals have supported this concept. With the increased advocacy of breastfeeding, the possibility of an increase in the prevalence of various autoimmune diseases seems a likely prospect. How could this be avoided? Here we show that the use of commercially available leuko-reduction filters placed either into nipple shields or into the nipples of bottles containing milk obtained by breast pump, makes the elimination of lymphocytes, shown to be allotypically incompatible, feasible. Morphologic and quantitative analyses of these observations will be presented.